Language Learning Strategies of Hong Kong And Malaysian Students - Andrew, Yau-hau Tse (2012)
Language learning strategies (LLS) that help learners enhance their language competence have played an important role in language learning; their spectrum has become one fertile area of research in second language acquisition (MacIntyre, 1994). The objective of this study is to investigate the LLS used by university students in Hong Kong and in Malaysia. Oxford’s (1990) Strategy Inventory for Language Learning (SILL) was used as the research instrument. The findings reveal that Hong Kong students use compensation strategies (medium use) and Malaysian students adopt memory strategies (low use) in learning English. To conclude, Hong Kong students used LLS in medium use, with no high use; whereas Malaysian students used LLS in low use, with no high or medium use. Finally, recommendations on LLS are proposed for ESL teachers.